Management of Concomitant Abdominal Aortic Aneurysm and Intra-abdominal, Retroperitoneal Malignancy - Treska, Vladislav; Molacek, Jiri; Certik, Bohuslav; Houdek, Karel; Hosek, Petr; Soukupova, Veronika; Stogerova, Christiana; Svejdova, Aneta (In vivo (Athens, Greece), 2021)
BACKGROUND/AIM: As the population ages, there are increasing findings of coincidental diseases such as abdominal aortic aneurysm (AAA) and intra-abdominal, retroperitoneal malignancy. The aim of this study was to propose an optimal treatment procedure for these patients. PATIENTS AND METHODS: Over a twenty-year-period, surgery was performed on a total of 1,098 patients with AAA and 32 (2.9%) patients with AAA and intra-abdominal, retroperitoneal malignancy: 18 renal, 6 colorectal carcinomas, 3 carcinomas of the small intestine, 3 primary liver tumours, 1 stomach carcinoma and 1 teratoma. The median age of patients was 72.5 years, there were 20 men (62.5%) and 12 women (37.5%). A one-stage procedure was performed on 19 patients (59.4%), and a two-stage procedure on 13 (40.6%) patients. RESULTS: The average time of hospitalization was 12.4±6.9 days (median=11.0 days) for one-stage procedure, for a two-stage procedure 21.3±9.3 days (median=20.0 days), p=0.0045. Seven patients (21.9%) died within 30 days after the operation. All the deaths were in the group of one-stage procedures (p=0.0252). The 1-, 3- and 5-year overall survival for patients following one-stage and twostage procedures was 61.0/56.3/51.5% and 89.0/79.9/53.0% respectively (p=0.1199). CONCLUSION: Symptomatic disease must be resolved first. Two-stage procedures are the method of choice and offer better short-term results compared to one-stage procedures.
Keywords: retroperitoneální nádory; nádory žaludku; Aged; výsledek terapie; Carcinoma, Renal Cell; intra-abdominal; lidé; senioři; ženské pohlaví; Retroperitoneal Neoplasms; surgical procedures; Female; mužské pohlaví; karcinom z renálních buněk; Aortic Aneurysm, Abdominal; Kidney Neoplasms; Treatment Outcome; retroperitoneal malignancy; Humans; Abdominal aortic aneurysm; long-term results; Male; nádory ledvin; aneurysma břišní aorty; Stomach Neoplasms